Risky Play An Ethical Challenge - Kvalnes, Øyvind; Hansen Sandseter, Ellen Beate (Critical Cultural Studies of Childhood,, 2023)
This open access book brings together current childhood research and contemporary ethical theory to draw attention to how children depend upon a scope of action for risky play for their mental and physical development. In many countries, the opportunities for children to play away from adults' close attention have decreased. At both school and home, protection and avoidance of harm take increasing priority. This book draws a distinction between do-good ethics and avoid-harm ethics to highlight ethical tensions and dilemmas encountered by professionals who work with children, and suggests better ways to balance these ethical dimensions in approaching risky play. .